Systems thinking for business and management : principles and practice / Umit S. Bititci, Agnessa Spanellis. - Bititci, Umit S.; Spanellis, Agnessa (KoganPage, 2024)
This textbook offers an accessible overview of key systems thinking theories, principles and methodologies, providing a practical approach by applying these to contemporary business problems and challenges.